Bovine papillomavirus in Egypt: clinico-pathological features and molecular evolutionary analysis - Rouby, Sherin; Ewies, Samar (Veterinaria Italiana, 2023)
Bovine papillomatosis is an infectious viral disease of cattle characterized by development of benign cutaneous warts. The present study describes bovine papillomavirus infection in cattle on clinco-pathological and molecular bases and compares the identified strains with the previously characterized papillomavirus isolates in Egypt either of bovine or equine origin. Out of sixty examined cattle, skin lesions were collected from eleven clinically diseased cattle exhibiting typical papillomatosis clinical signs and subjected to histopathological and molecular identification. Histological sections showed well-developed papillary projections of squamous epithelium associated with fibrovascular stroma. Type 1 bovine papillomavirus (BPV-1) was identified in the cutaneous lesions based on the results of L1 gene-based PCR using degenerated primer followed by DNA sequencing. Comparative sequence and evolutionary analysis revealed that papilloma sequences (OP777901, OP777902, OP777903) obtained in the current study are clustered along with MW018705.1, MG547343.1isolated from cattle in Egypt in 2017/2018 and MT502095.1.1, and MT502105.1 isolated from equine in Egypt in 2019. Results prove the circulation of BPV-1 in the areas under investigation and shed light on the role of multispecies grazing in Egypt as a risk factor for transmission of BPV-1 from cattle to horses.